2008
DOI: 10.1007/s11249-008-9299-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon Content on the Mechanical Properties and Lubricated Wear Behaviour of Al–40Zn–3Cu–(0–5)Si Alloys

Abstract: In this work, one ternary Al-40Zn-3Cu and seven quaternary Al-40Zn-3Cu-(0.25-5)Si alloys were synthesized by permanent mould casting. Their microstructure, mechanical and lubricated wear properties were investigated using appropriate test apparatus and techniques. As the silicon content increased the hardness of the alloys increased, but their elongation to fracture decreased. Tensile strength of the alloys decreased with increasing silicon content following a sharp decrease and a slight increase. Among the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
1
29
0
3
Order By: Relevance
“…It is known that as the pressure increases the oil film thickness decreases in lubricated systems [1][2][3][4][19][20][21][22][23]. The decrease in the oil film thickness may cause metal-to-metal contact in the early stages of the wear tests [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that as the pressure increases the oil film thickness decreases in lubricated systems [1][2][3][4][19][20][21][22][23]. The decrease in the oil film thickness may cause metal-to-metal contact in the early stages of the wear tests [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that zinc-based alloys can be successfully replaced by aluminium-based alloys for tribological applications [1][2][3]. Extensive research on the aluminium-based alloys resulted in the development of ternary Al-40Zn-3Cu and quaternary Al-40Zn-3Cu-2Si alloys [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome these limitations, the change in chemical composition has been proposed 5) as an alternative. For instance, recently, it has been proposed 6) to change the base from zinc to aluminum. Replacing zinc with aluminum in the alloy system causes the formation of the stable (CuAl 2 ) with a tetragonal crystalline structure instead of the metastable " phase promoting a considerable higher ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Replacing zinc with aluminum in the alloy system causes the formation of the stable (CuAl 2 ) with a tetragonal crystalline structure instead of the metastable " phase promoting a considerable higher ductility. 6) Therefore, the purpose of this work was to investigate the effect of change in chemical composition on the microstructure and mechanical properties, hardness, in order to establish a relationship which enables us to assess the hardness in the as-cast and homogenized alloys.…”
Section: Introductionmentioning
confidence: 99%